The Genesis African-Identity-Crisis through Wole Soyinka’s Death and King’s Horseman (NOBEL: Journal of Literature and Language Teaching, 2021)
The main thrust of this study was to explore the genesis of the African identity-crisis from the (pre) colonial times to the post-colonial age. The colonialists revolutionized the cultural backdrop of Africa and imposed European values upon African natives. This affected the social, economic, and political identities in Africa. Today, the imagination of identity-crisis in the African continent is appalling. Notwithstanding her potential to grow socio-economically and politically due to the dispensation of emancipation, Africa is still at the periphery of identity-crisis.  This qualitative paper argued that the jeopardy of African culture bred identity crisis in the contemporary states of Africa that hinders the continent from progressing. The hegemony of Europeans threatened to bring African culture to a dead end. This is exemplified by Soyinka’s Death and the King’s Horseman, which mirrors the propagation of Western ideologies that Africans ultimately became infatuated with to a degree of perceiving their own culture as unsophisticated. This is developed through the wilful relinquishment of African cultural practices because of European intervention.